Prospective Examination of Outcomes Following Implantation with 3D Printed Custom Total Talus for Talar Avascular Necrosis - Joshua L. Morningstar BS; Daniel J. Scott MBA, MD; Christopher E. Gross MD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Ankle Introduction/Purpose: End stage talar avascular necrosis (AVN) is a difficult diagnosis to manage clinically. Management options will vary based on severity and functional goals with current treatments including conservative measures, hindfoot fusions, and total talus replacement (TTR). The induction of three-dimensional (3D) printing and computer-aided design (CAD) into orthopaedic surgery has increased the ability to treat this complex pathology through patient specific 3D printed talus replacements, while sacrificing less range of motion than joint fusions. This purpose of this study is to report prospectively collected clinical and patient reported outcome measures (PROMs) of patients implanted with a custom 3D printed TTR in a multi-institutional prospective study. Methods: Patients presenting to clinic for talar avascular necrosis at one of 8 institutions were prospectively enrolled and implanted with a custom 3D printed total talus replacement at both academic and private settings. Patients had demographics, range of motion (ROM), and PROMs collected preoperatively, at 6 weeks, 3 months, 6 months, and 12 months. PROMs included VAS pain score and Foot and ankle outcome score (FAOS). Adverse events were analyzed in patients with minimum 6 weeks of follow-up and the preoperative and follow-up PROMs for patients with minimum 6-month follow-up were analyzed. A total of 18 subjects (17 patients) were enrolled in the study, with all subjects reaching 6 weeks minimum follow-up and 10 patients achieving 6 months of follow-up. Results: The cohort was majority male (55.6%) with mean age 46.8±14.65 years and BMI 33.5±7.25 kg/m2. There were no adverse events related directly to the implant at 6-week follow-up. However, there were 2 serious adverse events (complications) documented, one case of wound dehiscence at 5 weeks postoperatively, and one deep wound infection at 2 weeks postoperatively. Subjects pain scores improved at 6 months postoperatively, with VAS scores statistically significantly decreasing (31.3 ± 31.83 points; p=.0222). All FAOS subscales showed significant improvement from preoperative to 6 months postoperatively with the greatest change coming in FAOS QOL (39.8 ± 28.06; p<.0001) followed by FAOS Pain (29.4 ± 25.13; p=.0004). (Table 1) Additionally, at 6 months postoperatively, 90% of patients indicated good or excellent satisfaction. Conclusion: Implementation of custom 3D printed total talus replacement was found to have low rates of short-term adverse events and proved to be safe and effective for the treatment of end stage avascular necrosis. Patients were largely satisfied at 6 months postoperatively and showed considerable